Entwining interactive fiction with technical writing to develop structured authoring competencies. (13th February 2023) - Terry, Robert
Abstract : Concerns about teaching structured authoring, which is the use of software in technical writing to allow automatic textual reuse and reassembly, have been woven into the debate about what role technologies should play in preparing technical writing students for 'real world' needs since the late 1990s (see Brumberger & Laurer, 2015; Carnegie & Crane, 2019; Kimball, 2015; Rainey et al., 2018). Vee (2017) and others have argued that fundamental aspects of writing software code, many of which parallel structured authoring, are now required literacies. Indeed, as Gentle (2017) demonstrates, the difference between those writing code and those writing structured authoring continues to shrink. Helping to develop technical writers to understand this overlap remains a significant challenge. This article suggests that this challenge might be met by using an open-source interactive fiction authoring platform called Twine, which provides many of the building blocks of structured authoring while teaching fundamental aspects of coding. However, this approach is not without its perils. Through analyzing the findings of a two-year study, this article identifies potential avenues for success as well as potential pitfalls to be mindfully considered.